A thermodynamic potential for barium zirconate titanate solid solutions. (December 2018) - Peng, Jinlin; Shan, Dongliang; Liu, Yunya; Pan, Kai; Lei, Chihou; He, Ningbo; Zhang, Zhenyu; Yang, Qiong
Abstract Barium zirconate titanate [Ba(Zrx Ti1−x )O3 ] solid solutions are promising lead-free ferroelectric materials that have received substantial interest. Thermodynamic analysis based on phenomenological Landau–Devonshire theory is a powerful method for theoretical investigation of ferroelectric materials, but cannot be applied to Ba(Zrx Ti1−x )O3 because there is no thermodynamic potential. In this paper, a thermodynamic potential for Ba(Zrx Ti1−x )O3 (0 ≤ x ≤ 0.3) solid solutions is constructed, and then a thermodynamic analysis carried out. The results accurately reproduce known phase structures and their transition temperatures, with good agreement with experimentally measured polarization, dielectric, and piezoelectric constants. It is found that Ba(Zrx Ti1−x )O3 solid solutions at room temperature have three phase boundaries, including a tetragonal–orthorhombic phase boundary atx = 0.013, an orthorhombic–rhombohedral phase boundary atx = 0.0798, and a rhombohedral–paraelectric phase boundary atx = 0.2135. The results also indicate that the chemical composition-induced ferroelectric–paraelectric phase boundary has superior electromechanical properties, suggesting a new way to enhance electromechanical coupling in Ba(Zrx Ti1−x )O3 solid solutions. Simulation: thermodynamic potential for solid solutions A thermodynamic potential for barium zirconate titanate solid solutions is constructed and three phase boundaries at room temperature are revealed. A collaborative team led by Yunya Liu from Xiangtan University in China perform theoretical analysis to successfully construct a thermodynamic potential for Ba(Zrx Ti1-x )O3 solid solutions. Using this potential, they carry out thermodynamic analysis to reproduce phase structures and transition temperatures that are in good agreement with experiments. They find three phase boundaries for Ba(Zrx Ti1−x )O3 solid solutions, including tetragonal-orthorhombic, orthorhombic-rhombohedral and rhombohedral-paraelectric. The results indicate that the chemical composition-induced ferroelectric-paraelectric phase boundaries have good electromechanical properties. The new thermodynamic potential may be applicable to predict phase structures and electromechanical properties in other systems.